EVALUASI PELEKSANAAN PEMBELAJARAN DARING MASA PANDEMI COVID-19 DI SD NEGERI 4 SURULANGUN KABUPATEN MUSI RAWAS UTARA TAHUN PELAJARAN 2020/2021 - imron imron (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to evaluate the implementation of the online learning process during the Covid-19 pandemic at SD Negeri 4 Surulangun, Musi Rawas Utara Regency. This research is a descriptive qualitative study which aims to describe the situation or seek facts and factual information. The subjects of this study were teachers of SD Negeri 4 Surulangun. The research data were collected using interview and questionnaire methods, then the data obtained were analyzed descriptively. Interpretation of the results of data analysis is carried out based on predetermined benchmarks. The results show that online learning has been carried out even though this online learning system has been running as desired, but there are some obstacles that occur. These constraints can include the need for internet access, parental support in guiding and the parents' time to accompany their children. There are several things that can be done to improve communication between teachers and parents of students in supporting online learning, namely by providing a proper understanding of online learning for students and parents through socialization, meetings and other meetings. Giving this understanding can be done with the material of the synergy of teachers, students and parents of students